Alpha Oscillations Related to Anticipatory Attention Follow Temporal Expectations - Rohenkohl, Gustavo (J Neurosci, 2011)
Temporal expectations have been shown to enhance visual analysis of task-relevant events, especially when these are coupled with spatial expectations. Oscillatory brain activity, particularly in the alpha band, has been implicated in regulating excitability in visual areas as a function of anticipatory spatial attention. Here we asked whether temporal expectations derived from regular, rhythmic events can modulate ongoing oscillatory alpha-band activity, so that the changes in cortical excitability are focused over the time intervals at which target events are expected. The task we used involved making a perceptual discrimination about a small target stimulus that reappeared from “behind” a peripheral occluding band. Temporal expectations were manipulated by the regular, rhythmic versus irregular, arrhythmic approach of the stimulus toward the occluding band. Alpha-band activity was measured during the occlusion period, in which no stimulus was presented, but target reappearance was anticipated in conditions of high versus low temporal expectation. Time–frequency analysis showed that the amplitude of alpha-desynchronization followed the time course of temporal expectations. Alpha desynchronization increased rhythmically, peaking just before the expected reappearance of target times. Analysis of the event-related potentials evoked by the subsequent target stimuli showed enhancement of processing at both visual and motor stages. Our findings support a role for oscillations in regulating cortical excitability and suggest a plausible mechanism for biasing perception and action by temporal expectations.